Effectiveness of Education Financing Management in Public and Private Schools: Policy Perspective and Implementation - Zainuddin Al Haj Zaini (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the effectiveness of educational financing management in both State and Private Madrasah Aliyah in East Java, emphasizing policy frameworks and implementation practices. A qualitative case study approach was employed, involving 25 informants across three Madrasah Aliyah. Data were collected through interviews and document analysis, focusing on financial planning, allocation, and accountability mechanisms. Findings reveal that State Madrasah Aliyah benefit from stable financial support through government funding, yet face limited budget flexibility due to bureaucratic constraints. Conversely, Private Madrasah Aliyah exhibits greater autonomy in financial management but struggle with financial sustainability, relying heavily on tuition fees (SPP) and donations. The role of school principals is pivotal in both settings, although private institutions encounter more significant transparency issues. Teacher welfare is closely tied to the efficiency of financial management practices. The contrast between financial stability and autonomy highlights the need for policy reform. Enhanced financial training for madrasah managers and the adoption of digital financial systems are critical for improving transparency and accountability. Increasing budget flexibility in state madrasahs and fostering strategic partnerships with private madrasahs are recommended to support long-term financial health. Optimizing financial management through transparent, flexible, and technology-driven policies can significantly enhance the quality of education in Madrasah Aliyah institutions.